KEEFEKTIFAN MODEL PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA GEOBOARD TERHADAP AKTIVITAS DAN HASIL BELAJAR LUAS DAERAH BANGUN DATAR KELAS V SD - Sifa, Nor Laila; Witanto, Yuli (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The lack of use of interesting and innovative learning models and media can contribute to low activity and achievement of students' mathematics learning outcomes. This study aims to: (1) analyze the difference in student learning activities between learning that applies the Two Stay Two Stray model with the help of geoboard media and learning that uses the Direct Instruction model with the help of flat building replicas; (2) examine the difference in student learning outcomes between the two learning approaches; (3) evaluate the effectiveness of the implementation of the Two Stay Two Stray model assisted by geoboard media on increasing student learning activities; and (4) to examine the effectiveness of the model on students' mathematics learning outcomes. This study uses a quasi-experimental method with a posttest-only control group design. This study involved 50 students as a sample, which included 26 students in the experimental class and 24 students in the control class. Data collection techniques include observation, interviews, documentation, learning activity questionnaires, and multiple-choice tests to measure learning outcomes. The collected data was analyzed using the Independent Sample t-Test and the One Sample t-Test. The results of the analysis using the Independent Sample t-Test on learning activities showed a tcount value of 2.274 which was greater than the ttable of 2.010, while the learning results showed a tcount of 3.310 > ttable of 2.010. Furthermore, the results of the One Sample t-Test on learning activities showed a tcount of 3.338 which was greater than the ttable of 2.059. The student learning results through the same test showed a tcal value of 4.464 > a ttable of 2.059. Based on these findings, it can be concluded that there is a significant average difference between the experimental class and the control class. Thus, the application of the Two Stay Two Stray learning model supported by geoboard media has proven to be effective in improving student learning activities and outcomes in mathematics. ABSTRAKKurangnya penggunaan model dan media pembelajaran yang menarik dan inovatif dapat berkontribusi terhadap rendahnya aktivitas serta pencapaian hasil belajar matematika siswa. Penelitian ini bertujuan untuk: (1) menganalisis perbedaan aktivitas belajar siswa antara pembelajaran yang menerapkan model Two Stay Two Stray dengan bantuan media geoboard dan pembelajaran yang menggunakan model Direct Instruction dengan bantuan replika bangun datar; (2) menguji perbedaan hasil belajar siswa antara kedua pendekatan pembelajaran tersebut; (3) mengevaluasi efektivitas penerapan model Two Stay Two Stray berbantuan media geoboard terhadap peningkatan aktivitas belajar siswa; dan (4) mengkaji efektivitas model tersebut terhadap hasil belajar matematika siswa. Penelitian ini menggunakan metode kuasi eksperimen dengan rancangan posttest-only control group design.. Penelitian ini melibatkan 50 siswa sebagai sampel, yang meliputi dari 26 siswa pada kelas eksperimen dan 24 siswa pada kelas kontrol. Teknik pengumpulan data meliputi observasi, wawancara, dokumentasi, angket aktivitas belajar, serta tes pilihan ganda untuk mengukur hasil belajar. Data yang terkumpul dianalisis menggunakan Independent Sample t-Test dan One Sample t-Test. Hasil analisis menggunakan Independent Sample t-Test terhadap aktivitas belajar menunjukkan nilai thitung sebesar 2,274 yang lebih besar daripada ttabel sebesar 2,010, sementara hasil belajar menunjukkan thitung sebesar 3,310 > ttabel 2,010. Selanjutnya, hasil uji One Sample t-Test terhadap aktivitas belajar menunjukkan thitung sebesar 3,338 yang lebih besar daripada ttabel 2,059. Adapun hasil belajar siswa melalui uji yang sama menunjukkan nilai thitung sebesar 4,464 > ttabel 2,059. Berdasarkan temuan tersebut, dapat disimpulkan bahwa terdapat perbedaan rata-rata yang signifikan antara kelas eksperimen dan kelas kontrol. Dengan demikian, penerapan model pembelajaran Two Stay Two Stray yang didukung oleh media geoboard terbukti efektif dalam meningkatkan aktivitas serta hasil belajar siswa dalam pembelajaran matematika.